A new species of hermit crab provisionally assigned to the genus Pagurus Fabricius, 1775 (Crustacea: Anomura: Paguridae) from the Ryukyu Islands, Japan - Komai, Tomoyuki (Zootaxa, 2025)
A new pagurid hermit crab species, Pagurus inflatus sp. nov., has been provisionally assigned to the heterogeneous genus Pagurus Fabricius, 1775. This new species is characteristic in its elongated right cheliped with a noticeably inflated and produced proximoventral surface of the carpus, while lacking secondary sexual modification. Two male specimens of the new species were collected from depths of 159–174 m off Amami-ohshima Island, Ryukyu Islands, southwestern Japan. While P. inflatus sp. nov. bears some resemblance to species of Goreopagurus McLaughlin, 1988 and of Spathapagurus Lemaitre & Felder, 2011, particularly in the structure of the right cheliped. A preliminary phylogenetic analysis using nucleotide sequences of the 16S rRNA gene did not support its close relationship to G. pearcei (Wass, 1963), the type species of Goreopagurus. Although no genetic data are available for species of Spathapagurus, the absence of short sexual tubes in males, as well as other features derived from the shield and ambulatory legs, set the new species apart from Spathapagurus.